2006
DOI: 10.1002/ab.20112
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of the velicer attitudes toward violence scale: evidence for a four‐factor model

Abstract: The factor structure of the Velicer Attitudes Toward Violence Scale [VATVS;Velicer, Huckel and Hansen, 1989] was examined in three studies. Study 1 (n 5 460 undergraduates) found a poor fit for a hierarchical five-factor model earlier advanced by Velicer et al. [1989], but a good fit for an oblique four-factor model. In Study 2, this alternative model was cross-validated in a confirmatory factor analysis of an additional 195 undergraduate students. In Study 3, the competing models were compared in terms of abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0
20

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 28 publications
11
63
0
20
Order By: Relevance
“…20 In the present study, females demonstrated lower beliefs justifying aggression; higher beliefs supporting alternative strategies. Change among yoga group females (93.68%) is more than the males (49.42%).…”
Section: Gender Impactsupporting
confidence: 41%
“…20 In the present study, females demonstrated lower beliefs justifying aggression; higher beliefs supporting alternative strategies. Change among yoga group females (93.68%) is more than the males (49.42%).…”
Section: Gender Impactsupporting
confidence: 41%
“…If this is the case, then only modest (if any) short-term desensitization should be expected to take place for these individuals. Additionally, previous studies have linked aggression to higher pro-violence attitudes and lower empathic responding [Anderson et al, 2006;Mehrabian, 1997;Miller and Eisenberg, 1988], which are both outcomes of desensitization. Because of their pro-violence attitudes and lower empathy or sympathy toward victims of violence, individuals with high trait aggression might score higher on cognitive desensitization and lower on emotional desensitization.…”
Section: Introductionmentioning
confidence: 98%
“…The fifth questionnaire was the Anderson's version (Anderson, Benjamin, Wood & Bonacci, 2006) of the Velicer Attitudes Toward Violence Scale ([VATVS], Velicer, Huckel & Hansen, 1989). Only items belonging to Pro-War Attitude dimension were selected.…”
Section: Pro-war Questionnairementioning
confidence: 99%
“…The third questionnaire was the Social Dominance Orientation questionnaire that comprised 16 items. The fourth questionnaire was the Anderson's version of the Pro-War Attitude questionnaire (Anderson et al, 2006) that comprised 11 items. Because it has been cross-nationally validated we selected the Schwartz's instrument to measure human values in the following surveys.…”
Section: Materials and Proceduresmentioning
confidence: 99%